Penerapan E-CRM Penjualan Sapi di Gapoktan Bina Tani Kepenghuluan Sintong - Siagian, Yessica; Sinaga, Hommy Dorthy Ellyany; M, Desma Erica Maryati (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Gapoktan Bina Tani Kepenghuluan Sintong is a group of farmers engaged in the business of livestock and selling cows, both beef cattle and live cattle for resale. Gapoktan Bina Tani Kepenghuluan Sintong provides cows of various types and sizes such as Simmental Cow, Angus, Brahma, and Limousin. Currently, Gapoktan Bina Tani Kepenghuluan Sintong already has many customers but has obstacles in marketing, promotion, sales, and customer data management activities. To maintain its business to compete with other competitors, Gapoktan Bina Tani Kepenghuluan Sintong must improve its business strategy. The methods used in this study are qualitative, with the type of research being descriptive and active. The purpose of descriptive research is to describe the business processes running in Gapoktan Bina Tani Kepenghuluan Sintong, which is then analyzed using the concept of E-CRM. The results of research on the implementation of E-CRM cow sales at Gapoktan Bina Tani Kepenghuluan Sintong can optimize marketing, sales, and improve service to customers.